Improvement of the Saw Cylinder of the Saw Gin Stand - Bobirmirzo Mirjalolzoda; Mutakhkhirkhon Abduvakhidov; Akmal Umarov; Shukhrat Usmonov (Genius Journals, 2024)
The article examines the problem of increasing the rigidity of the saw cylinder of a saw gin by changing the cross-section of its shaft. It has been proposed to use a hexagonal shaft instead of a round shaft. Calculations were carried out using the SolidWorks Simulation program. Performed static, frequency, fatigue, as well as equilibrium and SolidWorks – Design Insight analysis of two types of saw cylinders. The influence of the shaft shape on the static performance of saw blades has been studied. The results made it possible to use a hexagonal shaft for the saw cylinder of the saw gin
Keywords: Stress; Displacement; Deformation